Identification and Analysis of Influence of Quality Costs on the Percentage of Damaged Cans (A Case Study in PT Margo Redjo, Yogyakarta) - Linda Linda; Slamet Sudarmadji; Moch Maksum (Indonesian Association of Food Technologists, 1999)
In the present study, quality cost elements, such as: prevention cost including the prevention costs during can exhausting, seaming and sterilization; appraisal costs including the appraisal cost during can seaming, sterilization and product quality control; internal failure costs including rework costs and those due to thrown away product, are identified to obtain normal or undamaged (not inflating, croocked, and leak) can quality. Whereas the external failure cost is assumed to be inexist.The result of the research shows that the index of quality cost of Margo Redjo mushroom canning factory during 1997 has tended to decrease. For every Rp1.000.000,00 increase in prevention cost cause the percentage of the buckled can to decrease in exhausting phase (1,29%), in can seaming phase (9,78%), in sterilization (1,03%), and in cost or wage for quality control manager (2,94%). Whereas for every Rp.1.000.000,00 increase in appraisal cost during the can seaming will increase the damaged can to 1,73%. This shows that the increase in final product for the appraisal causes the rework cost to increase. The appraisal of the final product as fire fighting action is not capable of improving the damaged can percentage. The most influential quality cost element for the damaged can is the prevention cost during the can seaming phase (48,83%), QC manager salary (24,45%), appraisal cost during sterilization and final product quality control (22,60%) appraisal cost during the can seaming phase (20,14%), and prevention cost during the sterilization phase (17,64%). The optimum quality cost is obtained atIndimesian Food and Nutrition Progress, 1999 Vol 6, 110.Rp11.538.461,00 with the percentage of damaged can of 2,3%. This amount of quality cost gives the company to avoid the damaged can to 17%.